2013
DOI: 10.1007/s11010-013-1896-z
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 inhibition of peroxisome proliferator-activated receptor alpha expression is mediated by JAK2- and PI3K-induced STAT1/3 in HepG2 hepatocyte cells

Abstract: Interleukin-6 (IL-6) is the major activator of the acute phase response (APR). One important regulator of IL-6-activated APR is peroxisome proliferator-activated receptor alpha (PPARα). Currently, there is a growing interest in determining the role of PPARα in regulating APR; however, studies on the molecular mechanisms and signaling pathways implicated in mediating the effects of IL-6 on the expression of PPARα are limited. We previously revealed that IL-6 inhibits PPARα gene expression through CAAT/enhancer-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 80 publications
0
12
0
Order By: Relevance
“…Several important signaling pathways are in association with STAT3 activation, including MAPK/ERK [ 24 ], PI3K/AKT/mTOR [ 25 ], c-Src [ 26 ], and JAK pathways [ 24 ]. We next evaluated the effects of SC99 on these specific kinases including JAK2, ERK, AKT, mTOR, and c-Src by immunoblotting.…”
Section: Resultsmentioning
confidence: 99%
“…Several important signaling pathways are in association with STAT3 activation, including MAPK/ERK [ 24 ], PI3K/AKT/mTOR [ 25 ], c-Src [ 26 ], and JAK pathways [ 24 ]. We next evaluated the effects of SC99 on these specific kinases including JAK2, ERK, AKT, mTOR, and c-Src by immunoblotting.…”
Section: Resultsmentioning
confidence: 99%
“…The precise mechanism underlying CTACK/CCL27 suppression via STAT3 is unknown. Although STATs are transcriptional activators, they also appear to act as transcriptional repressors (Zhou and Waxman, ; Chew et al, ). Previous reports indicated that STAT3 acted as a transcriptional repressor to PPARα.…”
Section: Discussionmentioning
confidence: 99%
“…Several important signaling pathways are associated with STAT3 activation, including MAPK/ERK [18] , PI3K/AKT [19] , c-Src [20] , and JAK pathways [18] . Our previous studies showed that SC09 had no effects on these kinases with the exception of JAK2 in multiple myeloma cells [16] , we next confirmed the effects of SC99 on these kinases in platelets.…”
Section: Sc99 Inhibits Stat3 Signaling In Plateletsmentioning
confidence: 99%